Wolfberry prevented liver damage caused by anti-tuberculosis drugs associated with the YAP1/FXR pathway through gut microbiota - Wang, Dan; Xiong, Yajun; Liu, Zhihan; Song, Xiaoyong; Liu, Jiaojiao; Gong, Yanli; Li, Zhuanzhuan; Shi, Xinli (Frontiers in Microbiology, 2025)
BackgroundThe prevalence of anti-tuberculosis drug-induced liver injury (AT-DILI) is significant, with severe cases potentially leading to liver failure or mortality. Research indicates that first-line anti-tuberculosis drugs (ATDs), including rifampicin (RIF) and isoniazid (INH), cause a lasting disruption of gut flora, which is significantly associated with drug-induced toxicity. Wolfberry (Lycium barbarum L.) is frequently utilized in traditional Chinese medicine for the treatment of hepatic and renal disorders. The mechanism by which wolfberry prevents AT-DILI remains unclear. This work aimed to explore how wolfberry prevents AT-DILI by modulating the composition and functionality of intestinal microbiota and enhancing intestinal barrier integrity, hence elucidating its protective mechanism via the gut-liver axis.MethodsForty male Kunming (KM)mice were randomly allocated into four groups: normal, model, wolfberry and Polyenylphosphatidylcholine (PPC) group (n = 10/group). The normal group received ultrapure water via gavage daily, whereas the other three groups were administered ultrapure water, wolfberry decoction, and PPC via gavage three hours prior to RIF and INH daily for 21 days. Twenty additional mice were made pseudo-germ-free through a one-week oral injection of antibiotic (ATB) water, subsequently categorized into ATB and ATB + wolfberry groups. The remaining intervention strategies were identical to those previously mentioned. Subsequently, serum Alanine Aminotransferase (ALT) and Aspartate Aminotransferase (AST), serum and tissue Total Bile Acid (TBA) levels, and serum creatinine (CRE) levels were assessed. Intestinal contents were obtained for 16S rRNA sequencing, and pathological investigation was conducted on liver, kidney, and intestinal tissues. The expression levels of Yes-associated protein 1 (YAP1), Farnesoid X Receptor (FXR), and Cytochrome P450 Family 7 Subfamily A Member 1 (CYP7A1) in hepatic tissue were assessed.ResultsResults showed AT-DILI decreased beneficial gut microbiota abundance and increased CYP7A1 expression associated with the YAP1/FXR pathway. Wolfberry intervention enriched beneficial microbiota, increased goblet cells, upregulated tight junction protein ZO-1, and enhanced intestinal barrier function, while reducing serum ALT, AST, and TBA. Additionally, wolfberry increased nuclear YAP1 expression, activated FXR, and downregulated CYP7A1 to reduce TBA synthesis. The key finding is that after antibiotics clear the gut microbiota, wolfberry failed to activate the YAP1/FXR pathway.ConclusionWolfberry comprehensively prevented liver damage under the condition of gut microbiota presence by enhancing gut microbiota diversity, strengthening intestinal barrier function, associating with the YAP1/FXR pathway.